Lack of correlation between the costs of anticancer drugs and clinical benefits in Japan. Issue 12 (27th November 2018) - Satoh, Etsuko; Sasaki, Yasutsuna; Ohkuma, Ryotaro; Takahashi, Takehiro; Kubota, Yutaro; Ishida, Hiroo; Hamada, Kazuyuki; Kiuchi, Yuji; Tsunoda, Takuya
Abstract : Both overall survival (OS) and progression‐free survival (PFS) are primary endpoints of phase III studies of new anticancer drugs. Medical care expenditures, especially oncology drug prices, are rapidly increasing; however, the impact of oncology drug prices on OS and PFS is unclear. We analyzed the relationship between oncology drug prices and clinical outcomes in Japan. The costs of a full course or 1 year of treatment were estimated on the basis of the latest National Health Insurance Drug Price Standards, and the relationship between costs and improvements in OS or PFS obtained with each drug were analyzed. Cost‐effectiveness was compared between new‐class drugs and next‐in‐class drugs. We then developed a simple model for estimating the costs required to prolong OS and PFS by 1 day and used this model to compare cost‐effectiveness. Drug costs were not significantly related to treatment outcomes in terms of PFS or OS. There was no significant difference in the median cost between novel drugs and the next‐in‐class drugs ( P  = 0.39). The oncology drug cost required to prolong PFS by 1 day was more expensive than the drug cost required for prolong OS by 1 day. Prices of oncology drugs should be decided on the basis of actual clinical benefits for cancer patients, and the drug price evaluation process should be disclosed in Japan. Abstract : There is no correlation between price of anticancer drugs and overall survival.